2018
DOI: 10.1080/10408444.2018.1509941
|View full text |Cite
|
Sign up to set email alerts
|

Use of proteomics to detect sex-related differences in effects of toxicants: implications for using proteomics in toxicology

Abstract: This review provides an overview of results obtained when using proteome analysis for detecting sexbased differences in response to toxicants. It reveals implications to be taken into account when considering the use of proteomics in toxicological studies. It appears that results may differ when studying the same chemical in the same species in different target tissues. Another result of interest is the limited dose-response behavior of differential abundance patterns observed in studies where more than one do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Past proteomics studies on blood have indicated sex-related differences in mice treated with different toxicants (reviewed in ref ). To determine whether there was any sex-related proteomic difference in mice treated with various concentrations of ascorbate in drinking water, we identified and quantified proteins from the serum of our different groups of mice by mass spectrometry analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Past proteomics studies on blood have indicated sex-related differences in mice treated with different toxicants (reviewed in ref ). To determine whether there was any sex-related proteomic difference in mice treated with various concentrations of ascorbate in drinking water, we identified and quantified proteins from the serum of our different groups of mice by mass spectrometry analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Although the hippocampus is known to be important for declarative memory, how the hippocampus regulates aggression is less well understood. Proteomics, as a high-throughput technique, can indiscriminately study the protein response and behavior pattern under different stress conditions and is widely applied to gain a deeper understanding of drug action, which contributes to the exploration of the induction mechanism of drug-mediated toxicity and provision of potential biomarker candidates. Of note, to date, very few studies have employed a proteomic approach in revealing protein markers of aggressive behavior induced by PER. Therefore, the aim of our study was to determine whether administration of perampanel to mice would induce alterations in hippocampal protein profiles and to elucidate the possible neurobiological mechanisms of aggressive behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the awareness of gender as an experimental factor has increased with the emphasis on endocrine active chemicals, underscoring biochemical and physiological differences between the sexes [ 16 ]. Currently, omics approaches fully contribute to highlighting the gender-specific response to contaminant exposure [ 15 , 17 ], including in invertebrates. Indeed, Ji et al [ 18 ] observed a gender-specific metabolic response of mussel Mytilus galloprovincialis to the flame retardant BDE 47.…”
Section: Introductionmentioning
confidence: 99%